Physical activity motivations and psychological well-being among university students: a canonical correlation analysis - Zhong, Tao (Frontiers in Public Health, 2024)
With increasing concern about mental health issues and active lifestyles among university students, understanding the interplay between different physical activity motivations and various dimensions of psychological well-being is important. The present study aims to explore the canonical relationship between physical activity motivations based on self-determination theory and psychological well-being according to Ryff’s model in university students. Nine hundred and sixty-six Chinese university students participated in this study. A canonical correlation analysis was conducted using six variables of motivations as predictors of six variables of psychological well-being. The canonical correlation analysis yielded two canonical functions. The first canonical function, which was primary, indicated that intrinsic motivation, integrated regulation, identified regulation, and introjected regulation contributed the most to psychological well-being. The second canonical function indicated that a decrease in external motivation and amotivation accounted for an increase in personal growth. This study underscores the importance of elucidating the underlying motivations driving physical activity behaviors in order to enhance psychological well-being in this population.